Sourcing complexity factors on contractual relationship: Chinese suppliers’ perspective - Subramanian, Nachiappan; Abdulrahman, Muhammad D.; Rahman, Shams (Taylor & Francis Open, 2014)
To reduce cost and gain competitive advantage, original equipment manufacturers (OEMs) around the world have continued their aggressive sourcing from China. However, sourcing in China has never been a straightforward process and OEMs face both tangible and intangible sourcing complexities with significant negative impact on both expected positive benefits and their contractual relationships with the Chinese suppliers. We developed sourcing complexity model using comprehensive literature review and multiple case studies in various industries to understand the suppliers’ views on sourcing complexity in China. We employed Analytic hierarchy process technique to prioritise identified complexity factors and to derive managerial insights. Our results indicate that tangible complexity factors highly influence the Chinese suppliers’ contractual relationship with OEM’s. Number of suppliers available to OEM’s to procure a component is identified as a primary dominating tangible factor, while differentiation in technical capabilities and operational practices between OEMs and suppliers represents the second biggest issue for Chinese suppliers in establishing contractual relationship with OEM’s.